PENGARUH KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR KARYAWAN PERBANKAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERASI (Studi Pada Bank Nagari Cabang Pekanbaru) - Balqis, Sonia; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Study aimed to describe the influence of job satisfaction on organizational citizenship behavior banking employees with organizational commitment as a moderation variable (study in Bank Nagari branch Pekanbaru). Job satisfaction as variable (X), organizational citizenship behavior as variable (Y), organizational commitment as variable (Z). The menthod in this research is descriptive and quntitative using SPSS 21, where the sample use are 45 employees performed byproportionate stratified random sampling method and data collection technique through questionnaires. From the results of the data analysis that includes a test of validity, reliability, normality, multicolinearity, heteroscedasticity, autocorrelation, simple linear regression, moderation regression analysis, determination, test t, and test f. So it can be concluded that job satisfaction has a significant effect to organizational citizenship behavior of banking employees in Bank Nagari branch Pekanbaru, job satisfaction has a significant effect to organizational citizenship behavior of banking employees with organizational commitment as moderation variable in Bank Nagari branch Pekanbaru.Keyword : job satisfaction, organizational citizenship behavior, and organizational commitment